Effects of Metacognitive Listening Strategy Training on Listening Comprehension and Strategy Use of ESL Learners - Abdul Malik, Faridah (2011)
This study examines the role of metacognitive strategies in enhancing ESL students’ listening comprehension performance. It specifically investigates the effects of metacognitive listening strategy training on ESL learners’ listening comprehension and on their metacognitive listening strategy use. The different effects that the training might have on listeners with different levels of listening proficiency are also explored. Finally, it seeks to find out the different ways in which skilled and less-skilled listeners apply metacognitive listening strategies. This study employed a nonrandomised control-group pretest-posttest quasi experimental research design. This involved the administration of pretests in the forms of a listening test and a metacognitive listening strategy questionnaire, which measured the students’ baseline abilities in listening comprehension and their initial patterns of metacognitive listening strategy use. This was followed by a metacognitive listening strategy training which was conducted over a duration of 18 class hours. The quasi experiment was completed with the measurements of the effects of training through the students’ posttest listening comprehension scores and the posttest metacognitive listening strategy questionnaire responses. To complement the quantitative data from the experiment, qualitative information in the form of think aloud protocols were collected to provide insights into the learners’ ‘actual’ metacognitive strategy use which was measured by a pre and post training think-aloud sessions. The quantitative data sets obtained from the listening comprehension test scores and the metacognitive listening strategy questionnaire responses were analysed statistically using paired samples t test, independent samples t test and ANCOVA. The think aloud protocols were analysed both quantitatively, through comparisons of strategy use profiles, and qualitatively, through examining emerging patterns of how skilled and less-skilled listeners use the strategies. The findings of the study point to the positive effects of metacognitive listening strategy training. Eventhough the difference is not statistically significant, those underwent metacognitive listening strategy training did perform slightly better than those who did not. It is also found that the training has benefitted the less-skilled listeners more than the skilled ones. In terms of strategy use, the results show that those who underwent training have widen their strategy repertoire and used metacognitive listening strategy more frequently. However, the findings on how training has affected the strategy use of different levels of listeners are inconclusive. The questionnaire findings indicate that it was the less-skilled listeners who increased their strategy repertoire and used strategy more frequently. However, the think aloud protocols analyses produce contrastive findings: it was the skilled listeners who made more gains in terms of strategy repertoire and frequency of strategy use. Finally, the think aloud protocols show that the skilled and less-skilled listeners may employ the same types of metacognitive listening strategies and the less-skilled listeners may use these strategies more frequently, but, the skilled listeners were more successful at comprehension as their more developed metacognitive strategy use enabled them to better regulate their top-down and bottom-up listening processes. The study strongly suggests for the incorporation of metacognitive listening strategy training in the ESL listening classroom.